Atratividade e estudos de assembleias de rola-bostas (Coleoptera : Scarabaeidae : Scarabaeinae) - Bach, Andressa (2022)
Baited pitfall is the most used method to collect dung beetles. However, the use of baits can add error on community quantification, as there are significant sources of variation on attractiveness. Furthermore, there are idiosyncratic responses of species that may lead to sampling selection, by attracting mostly species that feed on a specific resource. Thus, the objective was to evaluate the attractiveness effect on the measure of species’ relative abundance and dung beetle assemblages’ metrics. We hypothesize that baits affect dung beetle assemblage data because attract a greater proportion of some species, and, consequently, could alter assemblages’ structure metrics. Dung beetle data sampled by flight interception trap (FIT) was used as a baseline to data sampled by pitfall baited with human feces, at three Brazilian Amazon primary forests (terra firme sites). In order to achieve the objective we i) identified species with differential attractiveness to human feces baits; ii) assessed alterations on their relative abundance; iii) evaluated attractiveness effects on assemblages’ metrics when Shannon, Pielou and Simpson indices are used. We observed three different levels of attractiveness: there are species poorly attracted, species mostly attracted and others greatly attracted but to a lesser degree. Most attracted species showed a greater proportional abundance within baited pitfall samples. Thus, attractiveness indirectly effects the assemblage quantification, implying on less diversity, less equitability and more dominance.